Pengaruh Ekstrak Daun Kelor yang Diekstraksi dengan Beberapa Jenis Pelarut sebagai Biostimulan terhadap Pertumbuhan Bayam Merah - Ayola Pajrita; Zozy Aneloi Noli; Suwirmen Suwirmen (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Using biostimulants in plant cultivation can increase plant growth and make plants more stress-resistant. Plant extracts are one source of natural biostimulants such as Moringa (Moringa oleifera L.), which contain secondary metabolites and plant growth hormones. In the process of plant extraction, the type of solvent used affects the quality of the resulting extract. This study aimed to determine the effect of biostimulants of Moringa leaf extract extracted with several types of solvents on the growth of red spinach (Amaranthus tricolor L.) This research was conducted from March to April 2022 in the Greenhouse and Plant Physiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Andalas, Padang. This study used a Completely Randomized Design (CRD) with four treatments and eight replicates. As treatment is a solvent for extracting moringa leaves consisting of without extract (A), Distilled water (B), Methanol (C), and Ethanol (D). The results showed that the solvent used to extract moringa leaves gave a significantly different effect on the number of leaves but had no significant effect on plant height, leaf area, root length, wet weight, dry weight, chlorophyll content, and anthocyanin content of red spinach plants. Extraction of moringa leaves with methanol and ethanol increases the number of red spinach leaves, which is 14.1 strands.